Transformasi Pesantren sebagai Pusat Penyebaran Islam, Alat revolusi dan Lembaga Pendidikan Islam - Muh. Mustaqim (At-Tajdid: Jurnal Ilmu Tarbiyah, 2017)
The article will discuss the transformation of pesantren as one of the central institutions of Indonesian Muslims. based on two main theories. The first theory was adopted from Abdurrahman Wahid on the transformation of education in pesantren and schools. Second, Karel A. Stenbrink's theory of convergence of pesantren. The results of the discussion resulted in the fact that Pesantren in Indonesia continues to exist until today by continuing to improve, increasing its capacity and improving the quality of its education and continuing to develop its educational reform both from the institutional side, the education system, to its pre-tool facilities. this refutes the stenbrink karel thesis about the convergence of pesantren. This is to answer the doubts stenbrink and Islamic thinkers will be the madness of pesantren face the development of the times. The process of transforming pesantren education is strongly influenced by political factors, governmental power, socio-cultural factors of society, as well as the effort to meet the contextual needs by trying to maintain the uniqueness of the uniqueness of the pesantren itself.